Quantitative Thinning Model with Particular Reference to Sal Forests of Changbhakhar Forest Division (Madhya Pradesh) - Suri, S. K. (Indian Forester, 1975)
This paper deals with the quantitative thinning model constructed on the basis of a regression equation developed between bole diameter and crown diameter of Sal (Shorea robusta). Strong positive correlation between bole diameter and crown diameter has been observed, the correlation co-efficient being 0.873. The scope and the method of applying quantitative thinning grades have been discussed.